Early Fractional Amplitude of Low Frequency Fluctuation Can Predict the Efficacy of Transcutaneous Auricular Vagus Nerve Stimulation Treatment for Migraine Without Aura - Feng, Menghan; Zhang, Yue; Wen, Zeying; Hou, Xiaoyan; Ye, Yongsong; Fu, Chengwei; Luo, Wenting; Liu, Bo (Frontiers in Molecular Neuroscience, 2022)
Migraine is a common primary headache disorder. Transcutaneous auricular vagus nerve stimulation (taVNS) has been verified to be effective in patients with migraine without aura (MWoA).However, there are large interindividual differences in patients’ responses to taVNS. This present study aimed to explore whether pre-treatment fractional amplitude of low frequency fluctuation (fALFF) features could predict clinical outcomes in MWoA patients after 4-weeks taVNS.Sixty MWoA patients and sixty well-matched healthy controls(HCs) were recruited, and migraineurs received 4-weeks taVNS treatment.Resting-state functional magnetic resonance imaging(rs-fMRI) data were collected and the significant differences of fALFF were detected between MWoA patients and HCs using two sample t-test.A mask of these significant regions were generated and used for subsequent analysis.The abnormal fALFF in the mask were used to predict taVNS efficacy for MWoA using a support vector regression(SVR) model combining with feature select of weight based on the LIBSVM toolbox.We found that (1) compared with HCs, MWoA patients exhibited increased fALFF in the left thalamus, left inferior parietal gyrus(IPG), bilateral precentral gyrus(PreCG), right postcentral gyrus(PoCG), and bilateral supplementary motor areas(SMA), but decreased in the bilateral precuneus and left superior frontal gyrus(SFG)/medial prefrontal cortex(mPFC);(2) after 4-week taVNS treatment, the fALFF values significantly decreased in these brain regions based on the pretreatment comparison. Importantly, the decreased fALFF in the bilateral precuneus was positively associated with the reduction in the attack times(r =0.357, p=0.005, Bonferroni correction, 0.05/5), while the reduced fALFF in the right PoCG was negatively associated with reduced Visual Analog Scale (VAS) scores (r =-0.267, p=0.039, uncorrected);(3) the SVR model exhibited a good performance for prediction (r=0.411, p<0.001),suggesting that these extracted fALFF features could be used as reliable biomarkers to predict the treatment response of taVNS for MWoA patients.The present study demonstrated that the baseline fALFF features have good potential for predicting individualized treatment response of taVNS in MWoA patients, and those weight brain areas are mainly involved in the thalamocortical(TC) circuits, default mode network(DMN) and descending pain modulation system (DPMS).This will contribute to well understanding the mechanism of taVNS in treating MWoA patients and may help to screen ideal patients who respond well to taVNS treatment.